Enhancing mung bean hydration using the ultrasound technology: Description of mechanisms and impact on its germination and main components - Miano A.C. (2016)
The authors are grateful to the São Paulo Research Foundation (FAPESP, Brazil) for funding the project no. 2014/16998-3 and JC Pereira B.Sc. scholarship (2014/26433-3); the National Council for Scientific and Technological Development (CNPq, Brazil) for funding the project no. 401004/2014-7 and MD Matta Jr. post-doctoral fellowship (158545/2015-0); Cienciactiva for the A.C. Miano Ph.D. scholarship, from the “Consejo Nacional de Ciencia, Tecnología e Inovación Tecnológica” (CONCYTEC, Peru; Contract 272-2015-FONDECYT) and Coordination for the Improvement of Higher Education Personnel (CAPES, Brazil) for the N Castanha M.Sc. scholarship. The authors are also grateful to the “Núcleo de Apoio à Pesquisa em Microscopia Eletrônica Aplicada à Pesquisa Agropecuária” (NAP/MEPA-ESALQ/USP) for the support and facilities of Electronic Microscopy. By describing an important process for pulses industrialization, the author pays tribute to the International Year of Pulses (2016) of the Food and Agriculture Organization (FAO) of the United Nations.